A case of an Infant with SARS‐CoV‐2 hepatitis early after liver transplantation. (25th June 2020) - Heinz, Nicole; Griesemer, Adam; Kinney, Joanna; Vittorio, Jennifer; Lagana, Stephen M.; Goldner, Dana; Velasco, Monica; Kato, Tomoaki; Lobritto, Steven; Martinez, Mercedes
Abstract: We present a case of a pediatric liver transplant recipient diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection four days after receiving a living donor liver allograft from her mother. The recipient was a 6‐month‐old with end‐stage liver disease due to biliary atresia and failed Kasai. The infant had an uncomplicated implantation, excellent graft function and down‐trending liver enzymes until developing fevers, diarrhea, and moderate respiratory distress requiring non‐invasive respiratory support. SARS‐CoV‐2 testing (nasal swab Polymerase Chain Reaction) was positive on post‐operative day (POD) 4. Liver enzymes peaked 1000 U/L (5‐fold higher than the previous day) on POD 6. Histology demonstrated a mixed picture of moderate acute hepatitis and classical elements of mild to moderate acute cellular rejection. Her hepatitis and respiratory symptoms improved coincident with completing treatment with hydroxychloroquine, reduced immunosuppression, and intravenous gamma globulin (IVIG).